HUBUNGAN INDEKS MASSA TUBUH DAN KEKUATAN OTOT KAKI DENGAN KELUHAN NYERI OTOT KAKI PADA BURUH ANGKUT BARANG (PORTER) DI STASIUN KERETA API PASAR SENEN KOTA JAKARTA - Novita Ayu Ningrum; Ekawati Ekawati; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2017)
Porter at Pasar Senen railway station still using manpower without any supporting tools on sustains both internal and external loads. So it causes muscle pain such as leg muscle pain. Leg muscle pain is often caused by pressure on the sciatic nerve, muscle tension or poor blood supply therefore narrowing the arteries that deliver blood to the leg. Leg pain can be caused by length of physical work such as moving goods only using muscle strength. This study aimed to analyze the relationship between body mass index and leg muscle strength with leg muscle pain of porter in Pasar Senen Station. This study is a quantitative research with cross sectional design. The instrument used is questionnaire (to collect personal data such as age, years of service and exercise habits also complaints of pain on leg) and Back Leg Chest Dynamometer (to measure the strength of the leg musdes). The study population was the entire porter Pasar Senen Station in total 175 people, with sample size of 64 people. Data was analyzed using Rank Spearman and Chi Square. The result showed that 54,7% of respondents who had leg muscle pain complaints, 43,8% had normal BMI and 42,4% had less leg muscle strength. The result of this research showed that there was no correlation between body mass index (p = 0,470) with leg muscle strength. There was correlation between leg muscle strength (p = 0,016) with leg muscle pain complaints. Therefore, this research recommended porters to do Leg muscle strengthening regularly to avoid muscle spasms and minimize the risk of leg muscle pain.